Acute prostatitis probably due to Listeria monocytogenes in an HIV-infected patient. (October 2015) - Roca, B; Díaz, MD; Roca, M
We report a unique case of acute bacterial prostatitis probably caused by Listeria monocytogenes in an HIV-infected patient. For the best of our knowledge, this is the first case reported of a patient with this association. Our case illustrates the protean clinical presentations that L. monocytogenes infections may adopt, particularly in immunocompromised patients.